Awareness of Health, Hygiene, and Sanitation among the Elementary School Teachers and Students: A Post Covid Status Survey - Pandey, Nutan (Voices of Teachers and Teacher Educators, 2022)
World-wide hundreds of millions of people have passed through and are still passing through the detrimental effects of Covid-19 pandemic. The outbreak of Covid-19 has taught us how dangerous squalid living conditions are for human life as they can kill, make us sick and make our lives miserable. Better healthcare can treat the symptoms but not be the cause of ill health. Personal hygiene and sanitation is recognized as the number-one way by which people can lower the risks of many diseases. School is the place where children spend most of their time and have a chance to learn about health, hygiene and sanitation. Whatever children learn in school, they directly impart in their families and possibly will disseminate in their upcoming generation as well. Here the roles of the teachers are central as their level of mindfulness will certainly determine the level of alertness amongst students. The study discussed through this research paper assessed the level awareness regarding health, hygiene and sanitation among the elementary teachers and students of three different boards i.e., CBSE, ICSE, U.P. of Lucknow city, post Covid- 19 reopening of schools. The main intention behind this study was to gather the information, whether or not we have taken any lesson after the peril. It was a descriptive study involving a purposive sample of 09 teachers and 90 students. Results highlighted that our current citizens are not at all prepared to fight against any health-related risk outbreak even post Covid-19.